Comparison of education group strategies and home visits in type 2 diabetes mellitus: clinical trial - Jéssica Caroline dos Santos; Daniel Nogueira Cortez; Maísa Mara Lopes Macedo; Edna Afonso Reis; Ilka Afonso Reis; Heloísa Carvalho Torres (Universidade de São Paulo, 2017)
ABSTRACT Objective: to compare the adherence and empowerment of patients with type 2 diabetes mellitus for self-care practices and glycemic control in group education strategies and home visits. Method: Clinical trial with ten randomized clusters, performed with 238 patients with type 2 diabetes mellitus distributed in group education, home visit, and control group. Socio-demographic data, glycated hemoglobin and those obtained from the self-care and empowerment questionnaires were collected. Statistical analysis was performed separately by educational strategy. Results: the mean age of the patients was 57.8 years old (SD = 9.4 years old), with a predominantly female participation (66.4%). Both strategies presented similar results regarding adherence to self-care practices and patient empowerment. There was also a reduction in glycated hemoglobin levels; however, only in the education group, the difference presented statistical significance (p <0.001). Conclusion: the strategies were effective; however, group education presented better glycemic control results in relation to the home visit. International registry: NCT02132338 and national: RBR-92j38t in the clinical trials registry.